(untitled) (PERcursos Linguísticos, 2026)
This article examines the role of semantic phenomena in the maintenance or disruption of gender binarism in Brazilian Portuguese, considering new forms of communication emerging in and from postmodernity. The main theoretical framework draws on the works of Lyons (1979), Bréal (1992), Cançado (2012), Escarpinete and Ferraz (2015), Ferrarezi (2019), and Freitag (2023). The analyzed corpus corresponds to the video entitled Colocamos uma mulher TRANS e uma FEMINISTA RADICAL para conversar (sem que elas soubessem), published on YouTube by the Spotniks channel. The objective was to examine the recurrence and discursive function of the semantic features under analysis in order to understand their role in shaping the meaning effects conveyed by the participants in the debate featured in the video. The findings indicate that semantic resources such as hypernymy, hyponymy, and vagueness may serve as strategies either to subvert or reinforce binarism. Conversely, antonymic relations, through complementarity, tend to be established with the purpose of reinforcing binary logic. This study seeks to contribute to the advancement of research on the relationship between semantics, identity, and gender.